Tourism Potential of Malaringgi Village Reviewed from Natural Tourism Objects and Development Strategies Based on SWOT Analysis - Sulistyani, Eko Tri; Alfaretha, Adhelia Wida (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
This study aims to examine the potential of natural tourism in Malaringgi Village, South Konawe Regency, and formulate a development strategy based on a SWOT analysis. The descriptive method is used by collecting primary data through interviews, observations, and documentation during the 2023 UGM KKN-PPM Period 4 activities, namely from December 18, 2023 to February 5, 2024. The results of the analysis show that Malaringgi Village has natural tourism potential including beaches and waterfalls. However, it still faces several challenges such as poor accessibility, lack of infrastructure for natural tourist attractions, and environmental problems. From the results of the analysis, four development strategies were formulated, namely Strength-Opportunity (SO), Strength-Threat (ST), Weakness-Opportunity (WO), and Weakness-Threat (WT). In the SO strategy, the potential of natural tourism will be packaged in a comprehensive tour package in collaboration with travel agents. The WO strategy involves increasing accessibility, training the community and village officials, increasing environmental awareness, developing tourism activities, giving official names, waterfall tourist attractions and increasing marketing. The ST strategy leads to the development of distinctive tourism icons to differentiate themselves from other destinations. Meanwhile, in the WT strategy, the priority is to provide proper evacuation routes in emergency situations or natural disasters. The 2023 UGM KKN-PPM Program Period 4 Malaringgi Sub-Unit also contributed to the implementation of the development strategies that have been made, such as adding tourist attraction locations to Google Maps, forming Pokdarwis, creating camping ground areas, and creating disaster evacuation routes. Thus, it is hoped that Malaringgi Village can become an attractive, sustainable natural tourism destination and have a positive impact on the local community.